Migration and the Canadian Labour Market - Strauss, Kendra (Labour / Le Travail, 2017)
This article reviews "Liberating Temporariness?: Migration, Work, and Citizenship in an Age of Insecurity," edited by Leah F. Vosko, Valerie Preston, and Robert Latham, "When Care Work Goes Global: Locating the Social Relations of Domestic Work," edited by Mary Romero, Valerie Preston, and Wenona Giles, and "Producing and Negotiating Non-Citizenship: Precarious Legal Status in Canada," edited by Luin Goldring and Patricia Landolt.